Blockage of STAT3 Signaling Pathway by Morusin Induces Apoptosis and Inhibits Invasion in Human Pancreatic Tumor Cells. Issue 3 (March 2016) - Kim, Chulwon; Kim, Jin Ho; Oh, Eun Young; Nam, Dongwoo; Lee, Seok Geun; Lee, Junhee; Kim, Sung-Hoon; Shim, Bum Sang; Ahn, Kwang Seok
Abstract : Objectives: Signal transducer and activator of transcription 3 (STAT3) is an oncogenic transcription factor implicated in carcinogenesis. Here, we investigated the role of morusin, the major prenylflavonoid, isolated from Chinese herbal medicine in abrogating the constitutive STAT3 activation in human pancreatic tumor cells. Methods: The effect of morusin on STAT3 activation, associated protein kinases, STAT3-regulated gene products, cellular proliferation, and apoptosis was examined. Results: Morusin specifically inhibited constitutive STAT3 activation both at tyrosine residue 705 and serine residue 727 in 4 pancreatic tumor cells. The inhibition of STAT3 was mediated through the suppression of activation of upstream JAK1, JAK2, and c-Src kinases. Morusin led to the accumulation of the cells in different phases of the cell cycle and caused induction of apoptosis and loss of mitochondrial membrane potential. Morusin downregulated the expression of various STAT3-regulated gene products; this correlated with induction of caspase-3 activation and anti-invasive effects. Treatment with the protein tyrosine phosphatase inhibitor pervanadate reversed the morusin-induced downregulation of STAT3, thereby suggesting the involvement of a protein tyrosine phosphatase. Conclusions: Morusin is a novel blocker of STAT3 activation and thus may have potential in negative regulation of growth and metastasis of pancreatic tumor cells.